Potencial antitumoral da Calotroipis procera Ait. in vivo E in vitro - Moura, Eraldo Salustiano (2005)
This study initially evaluated the cytotoxicity of hydroalcoholic extracts from the aerial sections of Calatropis procera Ait f., with hexane fractions, dichloromethane and Nbutanol, tested in five lineages of tumor cells (HL-60, CEM, MCF-7, HCT-8 and B-16) via the MTT method and the antimitotic action in sea urchin eggs with positive control of doxirrubicina. The action of the ethanolic extract on the stalk was also studied with the fractions, hexane, dichlomethane, ethyl acetate, acetone and methanol, using the MTT method in four lineages of cells (HL-60, CEM, HCT-8 and B-16). The antimitotic action was evaluated with sea urchin eggs using three extracts, ethyl acetate, acetate and methanol with positive control of doxirrubicana. The hemolytic test was carried out with five fractions, using mice red blood cells. The in vivo evaluation was performed with hexane fractions, dichloromethane, ethyl acetate, acetone and methanol, by intraperitoneal means in the 180 sarcoma and the methanol fraction was used via oral means on Ehrlic’s tumor. Hydroalcoholic and ethanolic fractions showed cytotoxic activity. The hexane fraction presented less activity than 1.8 μg/mL. N-butanol had a result lower than 1.0 μg/mL, except for the B-16 lineage, which did not present any action. In the ethanolic extract the ethyl acetate presented action lower than 2.5 μg/mL and acetone lower than 4.4 μg/mL and methanol lower 10.5 and did not present any action in the B-16 lineage. Inhibition of embryonic development in sea urchin eggs in the hydroalcoholic extract in the first division of dichloromethane presented the best action, with 42.80 μg/mL, in the third division and blastula N-butanol 23.40 and 24.0 μg/mL respectively. The ethanolic extract presented an important antimitotic action, showing inhibition in all phases of embryonic development with action lower than 4.8 μg/mL, and the ethyl acetate was the most active in all phases of division. In the hemolytic test the ethyl acetate fractions 80.51 μg/mL, acetone 133.4 μg/mL and methanol 132.1 μg/mL presented action in erythrocytic membrane. In the in vivo study of the 180 sarcoma tumoral inhibition was evaluated with the positive and negative control group, weighing and histological study of the organs: liver, spleen and kidney and tumor. The organic fraction ethyl acetate presented inhibition in tumoral growth by 64.3%. As for the methanolic fraction 500 mg/kg (orally) presented inhibition by 43.18%.